Differential GABA concentration gradients are present in the edible parts of greenhouse melon (Cucumis melo L.) during all four seasonal croppings. Issue 2 (1st February 2019) - Toyoizumi, Tomoyasu; Ohba, Seiji; Fujii, Kyo-suke; Ikegaya, Atsushi; Matsuura, Hideyuki; Nakajima, Teruko
ABSTRACT: Food-derived gamma-aminobutyric acid (GABA) exhibits health-promoting benefits, and melon contain high GABA concentrations. Greenhouse melons ( Cucumis melo L. "Earl's Favorite") cultivated in Japan have identical or more edible parts than cultivars in other countries, however GABA distribution and the effects of seasonal variations are unclear. Thus, the present study aimed to evaluate GABA concentration gradients in four seasonal melons and how glutamic acid (Glu) influences the establishment of these gradients. GABA concentration was significantly lower near the exocarp than in the peduncle, equator, and remnant style regions in most seasons. Glu and GABA concentrations showed similar trends and were significantly correlated near the remnant style. No significant differences in GABA and Glu concentration were detected at concyclic sites across horizontal sections. These data indicate that GABA and Glu concentration differs substantially along a vertical melon section, but less so along a horizontal section, among sampling regions, sites, and cropping season. Graphical abstract: : GABA concentration differs substantially along a vertical melon section, but less so along a horizontal section.